The Orgnisation Performance and the Culture of Fun: Review in Changing World - Eshehri, Abdulrhman; Alsoaery, Abdulrahman (Archives of Business Research, 2023)
In the contemporary business landscape, organisations around the world are increasingly giving priority to improving the work environment. This effort is seen as vital to the success or failure of the organisation, with many focusing on modern, innovative designs and the integration of social and recreational activities to create a more positive workplace. While these strategies aim to enhance employee satisfaction, productivity, and innovation by alleviating work stress and promoting a positive attitude, there is also discussion about the potential negative aspects of this culture of fun. The article will explore the pros and cons of these practices, review their impact on both employees and organisations, and include relevant examples.